The effect of hardness on bending value in manufacturing brake pads from shell and palm fiber - Kholidah Agustina; Mulkan Iskandar Nasution; Ridwan Yusuf Lubis (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
Motorbikes are one of the primary needs for many people because they are more effectively used to carry out community activities than public transportation. Because motorbikes are used so frequently, the braking system is one of the parts that must be updated. Brake pads are motorbike equipment that function to slow and stop the vehicle comfortably. The research aims to determine the characteristics of brake linings and the optimal composition of brake linings that are good for use. Brake pads are a component of motorcycle vehicles that are useful for slowing down and stopping the speed of the vehicle comfortably. The purpose of this study is to find out how the characteristics of palm shells and fibers if used as material for making brake linings. The method used is direct experimentation with a qualitative approach. The results obtained are the characteristics of brake pads made from filler palm shell powder and palm fiber with polyurethane matrix have a hard texture, solid brown, if viewed from the surface of the brake lining is a little rough because the fiber is too long. The test results showed the best hardness value of 91 R and the best bending test with a value of 10.21 kgf/mm2